A new adsorption energy-barrier relation and its application to CO2 hydrogenation to methanol over In2O3-supported metal catalysts. Issue 7 (4th January 2023) - Yang, Deshuai; Lu, Huili; Zeng, Guixiang; Chen, Zhao-Xu
Abstract : A new thermodynamics-kinetics relation called adsorbate-dependent barrier scaling (ADBS) relation is discovered and used to predict the catalytic activity of a series of In2 O3 -supported metal and alloy catalysts for CO2 hydrogenation to methanol. Abstract : Herein, we report a new adsorption energy-barrier relation, the adsorbate-dependent barrier scaling (ADBS) relation, with which the catalytic activity of In2 O3 -supported metal catalysts for CO2 hydrogenation to methanol is predicted. It is shown that Cu, Ga, NiPt and NiPd alloys exhibit high catalytic activity for CO2 hydrogenation to methanol.